2007
DOI: 10.1007/s11894-007-0059-3
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel bacterial overgrowth: A negative factor in gut adaptation in pediatric SBS

Abstract: Small bowel bacterial overgrowth (SBBO) is common in infants and children with short bowel syndrome (SBS). Its occurrence is due to alterations in anatomy, motility, and secretion, which promote the abnormal growth of bacteria. SBBO is associated with significant clinical problems, including prolonged dependence on parenteral nutrition, liver injury, and malabsorption. A major clinical challenge is in making the correct diagnosis of bacterial overgrowth. Management of this disorder is still poorly understood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 53 publications
3
43
0
1
Order By: Relevance
“…2 Additionally, overgrowth of such organisms is associated negatively with bowel adaptation. 23 The fact that these organisms became less prominent in our study is somewhat unexpected, but the possibility exists that a 50 % SBR is insufficient to induce such changes, as these mice neither develop dilated loops of bowel nor require parenteral nutrition for survival.…”
Section: Discussionmentioning
confidence: 60%
“…2 Additionally, overgrowth of such organisms is associated negatively with bowel adaptation. 23 The fact that these organisms became less prominent in our study is somewhat unexpected, but the possibility exists that a 50 % SBR is insufficient to induce such changes, as these mice neither develop dilated loops of bowel nor require parenteral nutrition for survival.…”
Section: Discussionmentioning
confidence: 60%
“…The presence of overgrowth, as detected by the exhaled H 2 test has been described in 0-12.5% in the asymptomatic (20) volunteer group. However, it is important to note that the actual prevalence of the syndrome is not well known due to remaining difficulties for its diagnosis in daily practice (2) .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that although the gold standard for the diagnosis of overgrowth is still the presence of 1 x 10 5 to 10 6 colony forming units/mL (cfu/mL) in the jejunal aspirate, this definition has been challenged in the present scenario (2,5) . Khoshini and collaborators suggest that healthy individuals rarely have higher bacterial counts than 1 x 10 3 cfu/mL, which should be the new threshold for definition of the syndrome (8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated a shorter duration of the migratin motor complex cycle and feed pattern after resection [26]. Since bowel dilatation is a natural sequel of adaptation, surgery should be deferred unless dilatation causes recurrent episodes of bacteremia [27]. Bowel dilatation occurs more commonly in younger patients, who are more often candidates for surgical rehabilitation than adults [28].…”
Section: Intestinal Adaptationmentioning
confidence: 99%